Alternatif Media Dakwah di Era Digital - Efendi, Erwan; Nasution, Nurhalisah; Azza Mifta Rao (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
Technological developments in the digital era have influenced the da'wah model to develop increasingly rapidly. One of the technological trends in this millennial era is digital media because it is faster and easier to access information. Da'wah is calling, summoning, inviting and encouraging someone to do good things. Da'wah must be able to use it well and to the maximum extent possible. If not, preaching will be left behind and slow down, which will affect the morals and morals of the millennial generation. This article discusses whether alternative media for preaching in the digital era can attract the millennial generation in preaching. Podcasts are one of the media of choice for preaching in this modern era which is full of technological sophistication. This article aims to see that podcast media has become an option for conveying da'wah material in increasingly modern times. Podcasts were chosen because of their practical form, they can be listened to at any time and can even be collaborated with various other platforms in online media. Podcasts are an advanced means of preaching apart from conventional preaching activities.